2000
DOI: 10.1128/jvi.74.13.6223-6226.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of a Poliovirus/Hepatitis C Virus (HCV) Chimera: Interaction between the Poliovirus Cloverleaf and a Sequence in the HCV 5′ Nontranslated Region Results in a Replication Phenotype

Abstract: Internal ribosomal entry sites (IRESs) can function in foreign viral genomes or in artificial dicistronic mRNAs. We describe an interaction between the wild-type hepatitis C virus (HCV)-specific sequence and the poliovirus (PV) 5-terminal cloverleaf in a PV/HCV chimeric virus (containing the HCV IRES), resulting in a replication phenotype. Either a point mutation at nucleotide (nt) 29 or a deletion up to nt 40 in the HCV 5 nontranslated region relieved the replication block, yielding PV/HCV variants replicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…We found that expression of the luciferase gene was severely impaired in transfected cells when the full-length HCV 5Ј NTR was directly fused to the PV IRES, whereas no reduction of luc translation was observed with the other 5Ј variants (data not shown). This result indicated an interference between the HCV and the PV RNA elements similar to what was recently found with a recombinant PV that carries an HCV IRES to direct translation of the PV polyprotein (56).…”
Section: Vol 75 2001supporting
confidence: 58%
“…We found that expression of the luciferase gene was severely impaired in transfected cells when the full-length HCV 5Ј NTR was directly fused to the PV IRES, whereas no reduction of luc translation was observed with the other 5Ј variants (data not shown). This result indicated an interference between the HCV and the PV RNA elements similar to what was recently found with a recombinant PV that carries an HCV IRES to direct translation of the PV polyprotein (56).…”
Section: Vol 75 2001supporting
confidence: 58%
“…On the other hand, deletions up to nucleotides 27, 17, and 9 resulted in medium, small, and minute plaque sizes, respectively. The authors explained this phenomenon on the basis of a putative interaction between the HCV sequence up to nucleotide 31 and the poliovirus cloverleaf, which plays a key role in polioviral replication (Zhao et al 2000). However, on the basis of the present study, we suggest that this phenomenon may be, at least in part, attributed to long-range RNA-RNA interaction, which inhibits HCV Interaction between 5NTR and coding region of HCV www.rnajournal.org IRES-dependent translation, as the HCV sequence nucleotides 428-442 was present in the chimeric viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Translation of the polyprotein is directed by an internal ribosomal entry site (IRES) spanning most of the 5Ј nontranslated region (5ЈNTR) in combination with a portion of the core-coding region that augments the IRES-dependent translation (Tsukiyama-Kohara et al 1992;Wang et al 1994Wang et al , 2000Rijnbrand et al 1995;Honda et al 1996a;Lu and Wimmer 1996;Hwang et al 1998;Zhao et al 2000). With the exception of small hairpin structures located within the most 5Ј segment of the 5ЈNTR (domain I), all of the predicted stem-loop structures are essential for the internal initiation directed by HCV IRES (Wang et al 1994(Wang et al , 1995Rijnbrand et al 1995Rijnbrand et al , 2001Honda et al 1996a,b;Kamoshita et al 1997;.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, desired foreign antigens could be incorporated without size restriction; however, the recombinant virus is replication defective and requires a helper virus or capsid protein-expressing system for each cycle of propagation (12,30,34,35). The propagation-defective viral vector is attractive for its safety feature, even in the neuronal delivery of cytokine (8), but may also pose obstacles for inducing vigorous immune responses.The third strategy focused on construction of the dicistronic genome by placing a foreign insert together with the 5' noncoding internal ribosome entry site (1,2,24,27,45), but this vector strategy was flawed by frequent observation of the gradual deletion of the foreign gene in the early stages of serial passage. The cause of the genetic instability was not determined, but it was apparently related to the spatial restriction of the PV capsids.…”
mentioning
confidence: 99%
“…The third strategy focused on construction of the dicistronic genome by placing a foreign insert together with the 5' noncoding internal ribosome entry site (1,2,24,27,45), but this vector strategy was flawed by frequent observation of the gradual deletion of the foreign gene in the early stages of serial passage. The cause of the genetic instability was not determined, but it was apparently related to the spatial restriction of the PV capsids.…”
mentioning
confidence: 99%